Film serials and the american cinema, 1910-1940 : operational detection (2018)
The introductory chapter provides the book’s theoretical framework by de- tailing an anecdotal approach to the study of film history, and it addresses the shifting definition and function of the anecdote in historiography. The chapter furthermore introduces concepts of seriality in the context of nineteenth and twentieth-century modernity and establishes that, rather than reflecting processes of production and dissemination, serial narratives themselves activate and propel the processes of serialization and industrialization that enable their existence. Viewers approached serials with an awareness of their industrial and commercial character, and repetition assured their continued popularity across more than four decades rather than threatening to subdue it.